Decelerating to Accelerating Universe in f(R,T) gravity - Kumar Tiwari, Rishi; Beesham, A; Kumar Jaiswal, Ashit (Annals of Mathematics and Physics, 2026)
In this work, we study a Bianchi type-V anisotropic cosmological model in the framework of f(R,T) gravity by choosing the functional form. A variable deceleration parameter is considered, which yields the scale factor where c,d and n are positive constants. Exact solutions of the modified gravitational field equations are obtained. The model describes a transition from an initial decelerating epoch to the present accelerated phase for n > 1, whereas 0 < n < 10 corresponds to a continuously accelerating expansion. The dynamical behaviour of the cosmological parameters is investigated. The analysis shows that the anisotropy decreases with cosmic evolution and the model gradually approaches isotropy in the late-time regime. The cosmological term Λ(T) remains positive and dynamically evolves toward a small constant value in the asymptotic region. The energy conditions and sound speed criterion are satisfied throughout the evolution, supporting the physical acceptability and stability of the model. Furthermore, the statefinder trajectory (r,s) approaches the Λ CDM fixed point at late times, indicating consistency with observational cosmology.